THE IMPLEMENTATION DIGITAL MARKETING IN PROMOTING JATILUWIH TOURIST VILLAGE - I Made Darma Oka; Putu Widya Darmayanti; I Nyoman Winia; I Wayan Pugra (JURNAL KEPARIWISATAAN, 2024)
This research examines the implementation of digital marketing in promoting Jatiluwih tourist village. Data collection through observation, in-depth interviews with managers, and literature study using quantitative descriptive analysis. The sample is set as many as 75 people. The results showed that tourists know the existence of tourist villages through online media by 76.00% and offline by 24.00%. In detail, it is stated that from 76.00% of the use of online media, tourists stated that they chose tourist villages through information from social media by 52.00%, websites by 10.67%, search engines 2.67%, e-marketing 4.00%, and online advertising by 6.67%. This condition is proof that the implementation of digital marketing in marketing the Jatiluwih tourist village has proven to be able to have a positive impact on introducing and promoting the existence of a tourist village. It is hoped that in the future the management of the tourist village can use digital marketing media effectively in promoting the tourist village so that it is sustainable.